BERDAQ: LITERARY HERITAGE AND MODERN SIGNIFICANCE - Akramova Shahlo Rakhmonkul qizi (Modern American Journals, 2026)
This article examines the spiritual, social, and cultural significance of the literary legacy of Berdaq (Berdaq Qarg‘aboy o‘g‘li), a prominent representative of Karakalpak literature, in the context of modern society. The study focuses on the key themes of humanism, social justice, patriotism, moral responsibility, and enlightenment reflected in his poetic works. It highlights Berdaq’s role as a народный poet who voiced the concerns, aspirations, and ethical values of his people. The article demonstrates that Berdaq’s literary heritage remains relevant today as an important source of moral education, national consciousness, and social awareness, particularly for the younger generation.
Keywords: Berdaq, literary legacy, Karakalpak literature, humanism, patriotism, moral values, modern society.